2022
DOI: 10.21203/rs.3.rs-2351642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated gonadotropin levels are associated with increased biomarker risk of Alzheimer’s disease in midlife women

Abstract: Menopause has been implicated in women’s greater life-time risk for Alzheimer’s disease (AD) due to its disruptive action on multiple neurobiological mechanisms resulting in amyloid-β deposition and synaptic dysfunction.While these effects are typically attributed to declines in estradiol, mechanistic analyses implicate pituitary gonadotropins, follicle-stimulating hormone (FSH) and luteinizing hormone (LH), in AD pathology. In transgenic mouse models of AD, increasing FSH and LH accelerate amyloid-β depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…We have shown that MS-Hu6 has an acceptable affinity to FSH, with a K D of 7.2 nM that approaches trastuzumab; a long half-life of 7.8 days in humanized Tg32 mice; limited, but measurable accumulation in the brain upon subcutaneous injection; and thermal, colloidal, monomeric, structural and accelerated stability in formulation, as evidence of durability and manufacturability 30,41,42 . However, supporting our core concept of inhibiting FSH to prevent MCI is a recent study in women between ages 40 to 65, of which 35% were peri-menopausal--documenting a strong positive correlation between serum FSH levels and Aβ load (measured on PET scans) and gray matter volume in AD-vulnerable regions 43 .…”
Section: Discussionmentioning
confidence: 71%
“…We have shown that MS-Hu6 has an acceptable affinity to FSH, with a K D of 7.2 nM that approaches trastuzumab; a long half-life of 7.8 days in humanized Tg32 mice; limited, but measurable accumulation in the brain upon subcutaneous injection; and thermal, colloidal, monomeric, structural and accelerated stability in formulation, as evidence of durability and manufacturability 30,41,42 . However, supporting our core concept of inhibiting FSH to prevent MCI is a recent study in women between ages 40 to 65, of which 35% were peri-menopausal--documenting a strong positive correlation between serum FSH levels and Aβ load (measured on PET scans) and gray matter volume in AD-vulnerable regions 43 .…”
Section: Discussionmentioning
confidence: 71%
“…This supports testing of therapies regulating serum gonadotropin levels for AD risk reduction. Estrogen therapy with or without a progestogen is the treatment of choice for menopausal symptoms (Santoro et al, 2021) and holds promise for AD prevention (Levin-Allerhand et al, 2002;Nerattini et al, 2023). Observational studies generally report favorable effects of MHT on AD risk, whereas clinical trials indicate null effects on cognition in early post-menopausal patients and null or negative effects in older post-menopausal women (Maki, 2008;Jett et al, 2022a,b).…”
Section: Discussionmentioning
confidence: 99%